Hip joint moments during walking in people with hip osteoarthritis: a systematic review and meta-analysis. Issue 11 (November 2018) - Diamond, L.E.; Allison, K.; Dobson, F.; Hall, M.
Summary: Objective: This systematic review and meta-analysis investigated surrogate measures of hip joint loading during walking in people with hip osteoarthritis (OA). Methods: Five databases were searched up to January 14 th, 2018. Studies that measured hip joint moments in the frontal or sagittal plane during walking in people with hip OA and used either a healthy control group or the unaffected leg to compare hip joint moments were included. Standardised mean differences (SMD) in sagittal and frontal plane moments were pooled as appropriate, using a random effect approach. Methodological quality was assessed using the Downs and Black checklist. Results: Thirteen studies with 1, 141 participants were eligible and suitable for meta-analyses. Overall, people with hip OA had lower sagittal (SMD −0.55 (95% confidence interval (CI) −1.00 to −0.10) and frontal plane moments (SMD −0.63 (95% CI −0.92, −0.34) compared to controls. However, substantial heterogeneity was observed ( I 2 ≤ 89%). Results by disease stage suggest that people with end-stage hip OA have lower sagittal (SMD −0.96; −1.30, −0.61; I 2 = 69%) and frontal (SMD −1.17; 95% CI −1.71, −0.64; I 2 = 85%) plane moments compared to controls. People with less severe hip OA than end-stage disease have comparable sagittal (SMD 0.37; 95% CI −0.17, 0.90; I 2 = 69%) and frontal (SMD −0.24; 95% CI −0.76, 0.27; I 2 = 51%) plane moments compared to controls. Conclusion: Hip joint loading may be dependent on disease stage. People with end-stage hip OA under-loaded compared to controls, while those who were not awaiting hip joint replacement had comparable hip joint loads to controls.